Influence of occupation on median nerve cross-sectional area in apparently healthy volunteers - Anthony Chukwuka Ugwu; Benjamin Effiong Udoh; Alhaji Modu Ali; Mohammed Abba; Emmanuel Buba; Mohammed Yusuf Mohammed (Indian Journal of Health Sciences and Biomedical Research KLEU, 2017)
Background: Sonographic measurement of the median nerve has been proposed as a useful alternative to the electrodiagnostic test in the diagnosis of the carpal tunnel syndrome because of its ability to reveal morphological changes. Objective: The objective of this study was to investigate the influence of occupation, gender, and hand dominance on the median nerve cross-sectional area (MNCSA). Methodology: One hundred and eighty apparently healthy volunteers were recruited for the study. Hand dominance was ascertained in all volunteers. The device used was Voluson P8 ultrasound system with a 12-MHz transducer, using custom preset for musculoskeletal ultrasound. The Anteroposterior (D1) and transverse (D2) diameters of the median nerve were taken bilaterally at the level of the pisiform bone at the anterior surface of the wrist joint. Using these values, the MNCSA was calculated using the ellipse Formula. Results: The volunteers were divided into repetitive and nonrepetitive groups. The MNCSA was significantly higher (P < 0.05) in the repetitive work group than in nonrepetitive work groups. Similarly, a significant difference in mean MNCSA was noted between male and female volunteers in both groups. Again, a significant difference in mean MNCSA was observed in dominant and nondominant hands in the repetitive work group (P < 0.05). However, there was no significant difference in mean MNCSA in the nonrepetitive work groups (P < 0.05). Interpretation and Conclusion: A statistically significant difference in MNCSA was detected between repetitive and nonrepetitive work groups, male and female gender as well as in dominant and nondominant hands. Occupation, hand dominance, and gender, therefore, affect the cross-sectional area of the median nerve.